EVOLUTION OF HINDU ARCHITECTURE IN INDIA (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2025)
Hindu architecture in India has undergone a fascinating evolution over the centuries, reflecting the cultural, religious, and artistic influences that have shaped the landscape of the subcontinent. From the ancient temples of Khajuraho and Ellora to the majestic forts and palaces of Rajasthan, Hindu architecture has left a lasting impression on the architectural heritage of India. This essay aims to explore the evolution of Hindu architecture in India, tracing its development from the early Vedic period to the present day. Through an examination of key architectural landmarks and styles, this essay seeks to highlight the unique features and characteristics of Hindu architecture, as well as the historical and cultural significance of these structures.